PATH-27. GIANT CELL GLIOBLASTOMA DOES NOT REPRESENT A DISTINCT TUMOUR ENTITY BUT STRATIFIES INTO DIFFERENT GENETICALLY DEFINED SUBTYPES. (11th November 2019) - Wiedey, Anna; Dörner, Evelyn; zur Mühlen, Anja; de Azevedo Pinto, Maria; Kramm, Christof; Waha, Andreas; Pietsch, Torsten
Abstract: BACKGROUND: Giant cell glioblastoma (G-GBM) is a rare variant of glioblastoma (GBM) characterized by large often multinucleated tumour cells. G-GBM occurs most frequently de novo ; in contrast to IDH wildtype GBM they carry TP53 mutations in high frequency. METHODS: We collected 58 G-GBM from 25 children and 33 adults diagnosed at the Brain Tumor Reference Center of the German Society of Neuropathology and Neuroanatomy (DGNN) in Bonn, and performed a systematic histological, immunohistochemical and genetic analysis by molecular inversion probe array assay, panel next generation sequencing and pyrosequencing. RESULTS: 78.4% of G-GBM carried mutations of TP53 . Five G-GBM represented IDH -mutated gliomas, 5 cases had H3F3A-G34, and 3 had H3-K27M mutations. The vast majority (75%) lacked IDH or histone gene mutations. In these, chromosome 7 showed a copy number gain in 2/3 of the cases in contrast to the other molecular types. TERT promotor mutations occurred only in adult patients at a frequency of 35.5%. Similarly, chromosome 1q gain, 10 and 13 loss was more frequent in tumours of adult patients. MGMT promotor was methylated in 30.6 % of G-GBM. As a potential therapeutic target, PDGFR -alpha was found expressed in the vast majority of cases and its gene showed copy number gain in 34.5%. CONCLUSIONS: In summary, G-GBM is a histological phenotype most likely related to p53 dysfunction but can occur in different genetically defined GBM entities (IDH-, histone gene mutated or in IDH/histone wildtype GBM). (supported by grants from the Deutsche Kinderkrebsstiftung and the Medical Faculty of the University of Bonn, BONFOR)